The development of mobile application system on self-reflection for Muslims (iReflect) / Siti Fatimah Ismail - Ismail, Siti Fatimah (2018)
Self-reflection is like looking into a mirror and describing what you see on yourself. Generally, reflection means to think about something. Reflecting helps to develop skills and review the effectiveness, rather than just carry on doing things as always. This project is about developing mobile application system on self-reflection specifically for Muslims by fulfilling three (3) main objectives which are the first objective is to identify the user requirement for iReflect, to design iReflect and to develop iReflect mobile app. Meanwhile, from this mobile application, it will deliver benefits to two parties which are Muslims and mobile app developer. It brings benefit to Muslims since through this mobile application, it can assist them by being a platform for them to make self-reflection in order to redevelop themselves. Besides, as for developer, they can spread prosperous to Muslims by developing this useful application. Initially, the main problems that lead to iReflect development is the lack of interactive platform also inefficiency of the current approach for Muslims to make self-reflection. The problems are then examined thoroughly by conducting several interviews with expert and target users along with reviewing few of similar app as a preliminary study. Hence, iReflect then is developed by following five (5) out of seven (7) stages of Mobile Application Development Lifecycle (MADLC). Lastly, user testing is conducted in order to determine whether the requirements is fulfilled or otherwise also to point out the recommendations and future work that can be done.